ALTERNATIF STRATEGI PENGELOLAAN TAMAN WISATA ALAM KAWAH KAMOJANG KABUPATEN BANDUNG PROPINSI JAWA BARAT - Poppy Oktadiyani; E.K.S. Harini Muntasib; Arzyana Sunkar (Media Konservasi, 2005)
Kawah Kamojang (Kamojang Crater) Nature Recreational Park is located in Bandung Regency within West Java Province. With regards to various stakeholders managing and utilizing the area, an appropriate strategic management plan was considered necessary to be developed. Based on SWOT analysis, collaborative management seems to be a good alternative form of management strategy for the area.Key words : strategy, management, nature recreational park, collaborative, stakeholder